2016
DOI: 10.1088/0022-3727/49/7/075109
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the atomistic origin of X and W photoluminescence lines inc-Si fromab initiosimulations

Abstract: Abstract.We have used atomistic simulations to identify and characterize interstitial defect cluster configurations candidates to W and X photoluminescence centers in crystalline Si. The configurational landscape of small self-interstitial defect clusters has been explored through nanosecond annealing and implantation recoil simulations using classical molecular dynamics. Among the large collection of defect configurations obtained, we have selected those defects with the trigonal symmetry of the W center, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Details for these calculations can be found in Ref. [26]. It is worthy to note that I 3 -I, considered by Carvalho et al as W center, has the highest formation energy among I 3 defects considered in our study, and thus, it is the most unstable.…”
Section: About Here]mentioning
confidence: 72%
See 2 more Smart Citations
“…Details for these calculations can be found in Ref. [26]. It is worthy to note that I 3 -I, considered by Carvalho et al as W center, has the highest formation energy among I 3 defects considered in our study, and thus, it is the most unstable.…”
Section: About Here]mentioning
confidence: 72%
“…We resorted to ab initio simulations to determine if the I n selected from CMD simulations are compatible with radiative transitions of W and X centers. We used the vasp code [21,22] with PBE-PAW pseudopotentials [23,24] to characterize (i) the electronic band structure of defects, which shows whether a defect might favor or not radiative recombinations; (ii) the defect formation energy in order to obtain the defect levels within the energy band gap to relate them with experimental PL photon energies [25]; and (iii) the LVMs, which can be directly compared to the experimental values observed in PL spectra [26].…”
Section: About Here]mentioning
confidence: 99%
See 1 more Smart Citation
“…The Si selfinterstitial configurations included in this study were taken from those reported in the literature [11]. For the I2 clusters, we have used CMD simulations to identify and characterize the most common configurations [12]. CMD simulations were performed with the parallel code LAMMPS [13] and the Tersoff potential in its third parametrization.…”
Section: B Simulation Proceduresmentioning
confidence: 99%
“…It is believed to have a trigonal geometry 15 and be made up of interstitial silicon atoms [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%